Molecular and paleo‐climatic data uncover the impact of an ancient bottleneck on the demographic history and contemporary genetic structure of endangered Pinus uliginosa. Issue 3 (13th March 2020) - Łabiszak, Bartosz; Zaborowska, Julia; Wójkiewicz, Błażej; Wachowiak, Witold
Abstract: With the current rate of biodiversity loss, conservation management practices require a comprehensive understanding of eco‐evolutionary relationships, history, and genetic structure of species. Assessments of genetic diversity are crucial, especially in rare, endemic, or threatened forest tree species with small and isolated populations, such as peat bog pine ( Pinus uliginosa N.). Here, we used a novel approach, combining genetic diversity assessment, ecological niche modeling, and population demography inference to explore the complex history of a few remnant populations of this endangered pine. To asses the relative influence of isolation and fragmentation on genetic diversity in the taxonomic context, the patterns of genetic variation found in P. uliginosa were contrasted with those observed in its close relatives with much bigger distribution ranges and larger populations ( Pinus sylvestris, Pinus mugo, and Pinus uncinata ). We found a similar level of genetic diversity across the species at nuclear loci but contrasting patterns of variability distribution at chloroplast markers. We detected the signatures of an ancient genetic bottleneck dated at around 26 400 years ago, indicating a drastic reduction in the population size of P. uligionosa during the Last Glacial Maximum. In addition, we found substantial differentiation between current populations as a result of enhanced genetic drift during long‐lasting isolation. The research suggests potential conservation management strategies for peat bog pine and emphasizes the importance of using complementary approaches for their successful development.